Penerapan Model Pembelajaran Learning Cycle 5e Terhadap Hasil Belajar IPA Siswa Sekolah Dasar - ririn wahyuningsih; Yudi Budianti; Arrahim Aarrahim (Jurnal Elementaria Edukasia, 2023)
This research is motivated by the low science learning outcomes of elementary school children. Because students are less actively involved in learning activities, learning is still teacher-centered, and subject matter is only presented in textbooks, the low science learning outcomes in class are very concerning. Under these conditions, the Learning Cycle 5E learning paradigm might be able to help elementary school students improve their scientific learning. Students can actively participate in learning activities because they are incorporated in the Learning Cycle 5E learning paradigm. Using the systematic literature review (SLR) method, this study examines previous research on the impact of the 5E Learning Cycle model on scientific learning outcomes of elementary school students. This research sample analysis uses ten periodicals published between 2012 and 2022. The Learning Cycle 5E learning model can improve scientific learning outcomes of elementary school children, especially in higher grades, based on the findings and sufferings of literary studies. With the Learning Cycle 5E learning paradigm, students can actively participate in learning activities and cultivate a scientific learning mindset, so that learning is more relevant and allows them to achieve their learning goals. The conclusions from the research show that the Learning Cycle 5E learning model can greatly influence and improve scientific learning outcomes, so it is feasible to be applied in an educational environment. Based on the ease of analysis, there is a gradual change in the learning outcomes of the 5E Learning Cycle model. elementary School student.